2015
DOI: 10.1255/ejms.1359
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility—Mass Spectrometry-Based Screening for Inhibition of α-Synuclein Aggregation

Abstract: Aberrant protein folding and formation of amyloid fibrils are associated with numerous debilitating human diseases, for which there are currently no suitable therapeutic treatments. For instance, Parkinson's disease is characterised pathologically by the intraneural accumulation of the amyloid protein α- synuclein. In order to search for new therapeutic agents that are effective in preventing the early conformational changes that precede protein aggregation, it is necessary to devise new analytical screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…We previously reported that 2-D08 exerted a novel anti-aggregatory and neuroprotective effect against Aβ compared to transilitin and quercetin, which have A and C-ring hydroxylation (Marsh et al, 2017 ). In the present study, 2-D08 induced inhibition of αS aggregation and neuroprotection was as pronounced as myricetin, a generic amyloid aggregation inhibitor, and supports the idea that restricted B-ring tri-hydroxylation is adequate for targeting both αS and Aβ (Ono and Yamada, 2006 ; Hirohata et al, 2007 ; Zelus et al, 2012 ; Liu et al, 2015 ). From the TEM imaging, it appeared that transilitin modified the αSA53T fibrils in a similar way to myricetin, where only loose fibrils but no amorphous aggregates were seen.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We previously reported that 2-D08 exerted a novel anti-aggregatory and neuroprotective effect against Aβ compared to transilitin and quercetin, which have A and C-ring hydroxylation (Marsh et al, 2017 ). In the present study, 2-D08 induced inhibition of αS aggregation and neuroprotection was as pronounced as myricetin, a generic amyloid aggregation inhibitor, and supports the idea that restricted B-ring tri-hydroxylation is adequate for targeting both αS and Aβ (Ono and Yamada, 2006 ; Hirohata et al, 2007 ; Zelus et al, 2012 ; Liu et al, 2015 ). From the TEM imaging, it appeared that transilitin modified the αSA53T fibrils in a similar way to myricetin, where only loose fibrils but no amorphous aggregates were seen.…”
Section: Discussionsupporting
confidence: 86%
“…IM-MS is a sensitive tool for structural study of conformational folding and other characterization (Lanucara et al, 2014 ), and has been used for high-throughput screening of amyloid inhibitors (Young et al, 2014 ). It allows measurement of both the mass and collision cross section (CCS) of an ion, and thereby can provide information on the structural changes of amyloidogenic proteins such as αS during aggregation and binding of small molecules (Bernstein et al, 2004 ; Vlad et al, 2011 ; Liu et al, 2015 ). Combined with kinetic analysis of fibrillization (such as from thioflavin T fluorescence assays) and visualization of the fibrils using transmission electron microscopy (TEM), IM-MS provides insights on the effect of exogenous compounds on native αSA53T conformations in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any attempt to isolate aggregation intermediates to study their interactions causes disruption to this equilibrium and could result in alteration to the species present and an inaccurate representation of what is happening in the native heterogeneous system. Future experiments to probe association of 4554W with oligomeric aSyn species could include ion mobility mass spectrometry as utilized for a range of aggregating proteins ( Woods et al, 2013 ; Young et al, 2015 ), including aSyn ( Liu et al, 2015 ). Size exclusion chromatography enables isolation of oligomeric species ( Daturpalli et al, 2013 ; Schonhoft et al, 2017 ) and if coupled with small angle X-ray scattering can provide structural information ( Rekas et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The red blood pigment hemin ( 33 ) is a well-known inhibitor of Aβ aggregation [ 114 ]. Until recently, compound 33 was also thought to interfere with α-syn aggregation [ 115 , 116 ]. The effects of compound 33 on α-syn remain controversial; however, it has not been confirmed whether compound 33 inhibits ThT fluorescence via inhibition of α-syn aggregation or by obstructing the interaction between ThT and the proteins [ 117 ].…”
Section: Small Molecule Inhibitors Against α-Synuclein Aggregationmentioning
confidence: 99%